Die antike Münze als Fundgegenstand : Kategorien numismatischer Funde und ihre Interpretation - Thüry, Günther E., (Archaeopress, 2016)
This volume offers a detailed overview of ancient coin finds and their interpretation before offering a proposal for the categorisation of future numismatic finds.